Potassium leaching from thermopotash - Ivaniele Nahas Duarte; Hamilton Seron Pereira; Gaspar Henrique Korndörfer (Pesquisa Agropecuária Tropical, 2013)
Potassium losses by percolation or leaching can be reduced by using less soluble sources. This study aimed at evaluating leaching losses of potassium from granulated potassium chloride (KCl), granulated thermopotash and powdered thermopotash. The experimental design was completely randomized, with three replications, in a factorial scheme with four sources (control, granulated KCl, granulated thermopotash and powdered thermopotash) and two soil types (Ustoxic Quartzipsamment and Oxysol Red). The soil samples were added to lysimeters and moistened up to their field capacity. The potassium fertilizers were applied at 3,000 kg ha-1 of K2O, in the upper layer of the lysimeter, and incorporated to the first column ring (0,05 m), in all treatments. These columns were irrigated for 18 days, with water equivalent to a 344 mm rainfall. The soil solution was collected every two days and stored in 50 L containers. Potassium contents were determined in the leachate and in the soil, up to the depth of 0.8 m, at the end of the experiment. The potassium leaching was higher when KCl was the source used. The powdered termopotash supplied more potassium to the top soil layer (0-20 cm), while the KCl supplied more potassium to the subsurface layers, presenting a higher mobility in the soil profile, regardless of soil type. The granulated thermopotash released less potash to the top soil layer than the powdered thermopotash, while no significant differences were observed for the other layers.